Mahalanobis-taguchi system and time-driven activity-based costing integration of printed circuit board - Nurul Haziyani, Aris; Mohd Yazid, Abu; Sri Nur Areena, Mohd Zaini; Muhammad Arieffudin, Mohd Jamil; Nur Syafikah, Punueh; Wan Zuki Azman, Wan Muhamad; Faizir, Ramlie; Nolia, Harudin; Sari, Emelia (JATIT, 2023)
System integration involves creating or implementing a customized architecture, as well as integrating hardware, packaged and customized software, and communications. The electronic component demand is rising nowadays. However, a weekly rejection report for rejected parts is necessary in reflect the severity level as it can influence the criteria used to identify relevant parameters. Meanwhile, activity-based costing (ABC) is outdated since it employs interviews or surveys to get numerical data, which can lead to erroneous corporate data. This research aim is to integrate Mahalanobis-Taguchi system (MTS) with time-driven activity-based costing (TDABC) at the electronic component workstation. MTS optimizes 22 printed circuit board (PCB) assembly top side workstation environments. After generating time equation and capacity cost rate, TDABC considers critical elements to identify underutilized capacity. As a result, October and December have the most significant parameters (16) and August the fewest (10). Next, the TDABC confirmed that the PCB input into auto loader machine sub-activity has a large unused capacity of time (239,550 minutes) and cost (MYR18,120.67), which allows this workstation to minimize unused capacity by shifting employees to another load workstation. In spite of to minimize capacity utilization in sub-activity solder paste preparation, extra labor should be given since it has an overutilized capacity of time (-790,100 minutes) and cost (MYR-1,000,535.13). Lastly, the reduction of waste and better forecasting is obtained after MTS and TDABC integration is implemented.